The Promise of Youth Resistance Training - Faigenbaum, Avery D; Geisler, Stephan (B&G Bewegungstherapie und Gesundheitssport, 2021)
Global health reports indicate that a vast majority of children and adolescents are not accumulating the recommended amount of moderate to vigorous physical activity (MVPA) daily. This decline in MVPA has coincided with troubling temporal trends in muscular fitness in modern day youth. Since a prerequisite level of muscular strength is needed to move proficiently, developmentally appropriate interventions that target neuromuscular deficits are needed to prepare girls and boys for ongoing participation in active play, exercise and sport activities. Instead of focusing exclusively on aerobic activities, the promotion of youth physical activity should recognize the shared importance of strength, skill and aerobic activities for all youth regardless of body size or physical prowess. In addition to enhancing muscular fitness and improving motor skill performance, regular participation in resistance training has been found to have a favorable influence on musculoskeletal strength, cardiometabolic function, body composition, and mental health in children and adolescents. A new mindset that recognizes the critical importance of strength-building activities early in life is needed before this generation of girls and boys becomes resistant to exercise interventions later in life.
Keywords: Children; dynapenia; exercise; muscular strength; physical activity